Nonlinear phenomena and instability in semiconductors - L.V. Chirkova; E.V. Skubnevsky; K.T. Ermagambetov; E.T. Arinova (Қарағанды университетінің хабаршысы. Физика сериясы)
The nonlinear phenomena and instability in semiconductor structures are considered. Mechanisms of emergence of negative differential conductivity of N and S — types are described. As an example of education and use of drift not stability in semiconductors Gunn effect is considered. Operation of the generator of Gunn from the point of view of development of processes of self- organization in semiconductor structures is analysed. It is shown that the principle of its work is based on features of a power range of AsGa.